Co-Response of Atmospheric NO2 and CO2 Concentrations from Satellites Observations of Anthropogenic CO2 Emissions for Assessing the Synergistic Effects of Pollution and Carbon Reduction - Kaiyuan Guo; Liping Lei; Hao Song; Zhanghui Ji; Liangyun Liu (Remote Sensing)
Anthropogenic CO2 emissions are one of the primary drivers of the increase in atmospheric CO2 concentrations. It has been indicated that reducing emitted pollution gases can simultaneously bring out anthropogenic CO2 reduction, known as the synergistic effects of pollution and carbon reduction for controlling increases in CO2 and pollution gas concentrations. This study aims to assess these synergistic effects, which are still not clearly understood, by analyzing the mechanisms of atmospheric CO2 and NO2 concentration variability in response to human emission reduction activities. We utilize satellite-observed NO2, which is a short-lived anthropogenic pollution gas with the same emission sources as CO2, along with CO2 concentration data to detect their simultaneous response to anthropogenic CO2 emissions, thereby assessing and comparing the synergistic effects of pollution and carbon reduction in the two study areas of China and the United States, as well as in a special scenario of abrupt reductions in anthropogenic CO2 emissions. The results show that the synergistic effects of pollution and carbon reduction in the United States are likely better than those in China, as the United States demonstrates a stronger response (R2 = 0.53) between atmospheric NO2 and anthropogenic CO2 emission compared with China (R2 = 0.36). This difference is attributable to the CO2 emissions from coal-fired power generation in China are much more than those in the United States, where oil and natural gas dominate. Furthermore, the analysis of special scenarios during the COVID-19 pandemic (2020–2022) in China demonstrates that the types of anthropogenic emission sources are the main factors influencing the synergistic effects of pollution and carbon reduction. Specifically, the megacity regions, where fossil fuel power plants and transportation are the main emission sources, presented stronger synergistic effects of pollution and carbon reduction than those regions dominated by coal-based metallurgical and chemical plants.